Barriers and enablers to accessing support services offered by staff wellbeing hubs: A qualitative study - Keyworth, Chris; Alzahrani, Adnan; Pointon, Lucy; Hinsby, Kerry; Wainwright, Nigel; Moores, Lucie; Bates, Jenny; Johnson, Judith (Frontiers in Psychology, 2022)
Background International efforts have been made to develop appropriate interventions to support the mental health needs of healthcare professionals in response to COVID-19. However, fewer staff have accessed these than expected, despite experiencing elevated levels of mental distress since the onset of the pandemic. Consequently, we aimed to examine the barriers and enablers for healthcare professionals in accessing interventions offered by a Staff Mental Health and Wellbeing Hub. Methods Twenty-five semi-structured interviews were conducted with healthcare, social care and voluntary, community and social enterprise (VCSE) sector staff. Data were analysed using thematic analysis. Results Four key themes were identified: (1) Environment and Atmosphere in the Workplace; (2) The Impacts of COVID-19; (3) Confidentiality; and (4) Awareness and Communication of Resources. Organisational environments were perceived as an important enabler of accessing the hub services for mental health and wellbeing support. This included the importance of recognising and responding to the ongoing pressures of COVID-19- specific challenges. Ensuring and communicating aspects of confidentiality, and ensuring clear and consistent communication of the benefits of the Hub may encourage help-seeking for mental health challenges among healthcare professionals. Discussion Our findings highlight important considerations to increase uptake and engagement with services to support the mental health and wellbeing of healthcare professionals and associated staff and volunteers. Organisations aiming to increase employee uptake of these services should regularly circulate consistent and clear emails about what these services offer, provide training and information for managers so they can support staff to access these services and ensure access is confidential.